MANAGEMENT OF THE COMPANY’S BUSINESS REPUTATION THROUGH SOCIAL NETWORKS - Shymanska, Oksana; Dluhopolskyi, Oleksandr; Dluhopolska, Tetiana; Kolinets, Lesya; Farion, Demian; Lohush, Anzhela (Socio-economic relations in the digital society, 2024)
The article clarifies the theoretical aspects of managing the business reputation of companies in social networks. The relevance of the introduction of modern information and communication technologies into the business practice of business entities is substantiated. The goal is to research the strategy of forming the business reputation of companies in social networks and promoting a positive brand. The work uses such general scientific and special research methods as analysis, synthesis, systematic approach, generalization, grouping and classification, and expert evaluations. It is justified that today the influence on the behavior of the consumer regarding the purchase of a product or service is mainly based on trust. It has been established that no successful strategy for managing a company’s reputation on the Internet is complete without SEO as a process of adjusting the HTML code, text filling (content) of the site structure, and controlling external factors to meet the requirements of the search engine algorithm. Given that users typically gravitate towards the top search results, a higher ranking of the company’s website increases the likelihood of users navigating to it from the search engine. Also, the company’s rating in general is significantly affected by the brand’s reputation in social networks (both positive and negative). In general, trust in the company and the product itself from the consumer and counterparty becomes a key factor in the effective development of any business in the digital society. Qualitatively satisfied consumer needs lead not only to an increase in sales but also to the formation of brand loyalty and an increase in the company’s reputation in general. In addition, using social networks as a platform to communicate with consumers allows you to better understand their needs and desires.